Sol gel synthesis of TEOS-SiO2-PDMS hydrophobic film for ceramic coating - เพริศแก้ว, ธิดารัตน์; พันธ์สุขุมธนา, ลดา; ศรีหล่มสัก, สุธรรม; บางหลวง, วราลี (Bulletin of Applied Sciences, 2022)
Sol gel synthesis for ceramic hydrophobic coating was studied. Tetraethyl orthosilicate (TEOS) and Polydimethylsiloxane, (PDMS) were used to form the hydrophobic gel. Silica nano-particles, 12 and 20 nm, at 0.5, 5.0, or 10 wt.% and heat treatment at temperature 300 or 400 °C were varied in the synthesis of the hydrophobic and transparent films. The contact angle was used to measure the hydrophobic property and the transmittance was used to measure the transparent property of the films. The study showed that the coating could have the contact angle of 139° and transmittance of 73%. When the ceramic glaze was coated by the gel, water droplets on the surface were in spherical shape and flow away quickly. The effects of abrasion on the contact angle of the film coated on the smooth surface of ceramic glazes or on the uneven one were showing different results.